Stem Cell-Derived Human Intestinal Organoids as an Infection Model for Rotaviruses - Stacy R. Finkbeiner (American Society for Microbiology, 2012)
ABSTRACT Directed differentiation of stem cell lines into intestine-like tissue called induced human intestinal organoids (iHIOs) is now possible (J. R. Spence, C. N. Mayhew, S. A. Rankin, M. F. Kuhar, J. E. Vallance, K. Tolle, E. E. Hoskins, V. V. Kalinichenko, S. I. Wells, A. M. Zorn, N. F. Shroyer, and J. M. Wells, Nature 470:105-109, 2011). We tested iHIOs as a new model to cultivate and study fecal viruses. Protocols for infection of iHIOs with a laboratory strain of rotavirus, simian SA11, were developed. Proof-of-principle analyses showed that iHIOs support replication of a gastrointestinal virus, rotavirus, on the basis of detection of nonstructural viral proteins (nonstructural protein 4 [NSP4] and NSP2) by immunofluorescence, increased levels of viral RNA by quantitative reverse transcription-PCR (qRT-PCR), and production of infectious progeny virus. iHIOs were also shown to support replication of 12/13 clinical rotavirus isolates directly from stool samples. An unexpected finding was the detection of rotavirus infection not only in the epithelial cells but also in the mesenchymal cell population of the iHIOs. This work demonstrates that iHIOs offer a promising new model to study rotaviruses and other gastrointestinal viruses. IMPORTANCE Gastrointestinal viral infections are a major cause of illness and death in children and adults. The ability to fully understand how viruses interact with human intestinal cells in order to cause disease has been hampered by insufficient methods for growing many gastrointestinal viruses in the laboratory. Induced human intestinal organoids (iHIOs) are a promising new model for generating intestine-like tissue. This is the first report of a study using iHIOs to cultivate any microorganism, in this case, an enteric virus. The evidence that both laboratory and clinical rotavirus isolates can replicate in iHIOs suggests that this model would be useful not only for studies of rotaviruses but also potentially of other infectious agents. Furthermore, detection of rotavirus proteins in unexpected cell types highlights the promise of this system to reveal new questions about pathogenesis that have not been previously recognized or investigated in other intestinal cell culture models.